Strategi Pengembangan Desa Wisata Liang Pematang Di Kec. Sinembah Tanjung Muda Hulu Untuk Meningkatkan Kesejahteraan Masyarakat Kabupaten Deli Serdang - Bakti Gunawan (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2023)
This study aims to examine strategies for developing a tourist village in Liang Pematang Village, Deli Serdang Regency, as well as providing suggestions for improving local welfare/economy through a tourism village development strategy. The method used in this study was interviewing village officials and the people of Liang Pematang Village. Data analysis was performed using the SWOT analysis technique. From this study it was found that the facilities and infrastructure were still inadequate, meanwhile Liang Pematang Village also had quite good strength where the government and the people of Iang Pematang Village took an active role in developing Liang Pematang Village as a Tourism Village and could improve people's welfare. Furthermore, the strategy undertaken is to maintain and increase the potential that exists in the village of Liang Pematang